Heat shock protein 70 promotes cancer cell viability by safeguarding lysosomal integrity. - Gyrd-Hansen, M; Nylandsted, J; Jäättelä, M (2004)
The major heat-inducible Hsp70 is a potent survival protein that confers cytoprotection against numerous death-inducing stimuli and increases the tumorigenicity of rodent cells. The depletion of Hsp70 by adenovirus-mediated transfer of antisense cDNA induces caspase-independent death of tumorigenic cells while non-tumorigenic cells are unaffected, suggesting that Hsp70 has cancer-specific function(s). We have recently demonstrated that the depletion of Hsp70 in cancer cells results in a cysteine cathepsin-dependent death, which is preceded by lysosomal destabilization and release of lysosomal constituents to the cytosol. In line with this, Hsp70 localizes to the membranes of lysosomes in human colon carcinoma cells and immortalized murine embryonic fibroblasts (MEFs) and prevents lysosomal membrane permeabilization and cell death induced by tumor necrosis factor (TNF), etoposide and H2O2. These findings identify Hsp70 as the first survival protein that functions by stabilizing the lysosomal membrane.